The Long-Term Dynamics of the Incidence of Prostate Cancer in the Omsk Region - V. L. Stasenko; N. G. Shirlina; V. A. Shirinsky; N. V. Shirinskaya; T. M. Obukhova (Эпидемиология и вакцинопрофилактика)
The purpose of this study is to assess the dynamics of the incidence of prostate cancer in the Omsk region for the period 2006– 2017. Materials and methods. A retrospective epidemiological analysis of data from statistical reports (Form No. 7) of the Omsk Oblast health authorities for the period 2006–2017 was carried out. Results and its discussion. In the structure of oncological morbidity in the male population of the Omsk Region, the proportion of prostate cancer was 16.3% and was lower than the average Russian average (17%). In rural areas, compared with the regional center, higher rates of increase in the incidence of prostate cancer were observed (by 1.2 times). In general, the situation on the territory of the Omsk Region is similar to the global trend, characterized by an increase in the incidence of the male population of prostate cancer, which is a reflection of insufficient attention to primary cancer prevention, features of the socio-economic situation in the Russian Federation. Findings. 1. In the long-term dynamics of incidence of prostate cancer in the region for the period 2006–2017. there was a moderately pronounced upward trend in indicators (Tpr. = 3.94%; p < 0.05), with higher growth rates (1.2 times) in rural areas compared to the regional center (respectively, 3.56% and 3.04%; p < 0.001). 2. From 2006 to 2017 incidence of prostate cancer in the Omsk region increased 2.3 times in total (from 29.2 to 66.2 per 100 ths) and 1.8 times in standardized indicators (from 24.8 to 44.4 per 100 ths). 3. Despite the obvious relevance of the pathology, the prevalence of known risk factors for the development of prostate cancer in the Omsk Region has not been studied sufficiently, which requires scientific justification and improvement of approaches to primary prevention with regard to regional characteristics.